Effect of strain on voltage-controlled magnetism in BiFeO(3)-based heterostructures - Wang, J. J. (Nature Publishing Group, 2014)
Voltage-modulated magnetism in magnetic/BiFeO(3) heterostructures can be driven by a combination of the intrinsic ferroelectric-antiferromagnetic coupling in BiFeO(3) and the antiferromagnetic-ferromagnetic exchange interaction across the heterointerface. However, ferroelectric BiFeO(3) film is also ferroelastic, thus it is possible to generate voltage-induced strain in BiFeO(3) that could be applied onto the magnetic layer across the heterointerface and modulate magnetism through magnetoelastic coupling. Here, we investigated, using phase-field simulations, the role of strain in voltage-controlled magnetism for these BiFeO(3)-based heterostructures. It is predicted, under certain condition, coexistence of strain and exchange interaction will result in a pure voltage-driven 180° magnetization reversal in BiFeO(3)-based heterostructures.